Addition of Diquat Enhances the Electron Mobility in Various Non‐Fullerene Acceptor Molecules. (15th July 2022) - Nugraha, Mohamad Insan; Gedda, Murali; Firdaus, Yuliar; Scaccabarozzi, Alberto D.; Zhang, Weimin; Alshammari, Sanaa; Aniés, Filip; Adilbekova, Begimai; Emwas, Abdul‐Hamid; McCulloch, Iain; Heeney, Martin; Tsetseris, Leonidas; et al.
Abstract: Molecular doping of organic semiconductors is often used to enhance their charge transport characteristics. Despite its success, however, most studies to date concern p ‐doping with considerably fewer reports involving n ‐dopants. Here, n ‐doping of organic thin‐film transistors (OTFTs) based on several non‐fullerene acceptor (NFA) molecules using the recently developed diquat (DQ) as a soluble molecular dopant is reported. The low ionization potential of DQ facilitates efficient electron transfer and subsequent n ‐doping of the NFAs, resulting in a consistent increase in the electron field‐effect mobility. Solution‐processed BTP‐eC9 and N3‐based OTFTs exhibit significant increase in the electron mobility upon DQ doping, with values increasing from 0.02 to 0.17 cm 2  V –1  s –1 and from 0.2 to 0.57 cm 2  V –1  s –1, respectively. A remarkable electron mobility of >1 cm 2  V –1  s –1 is achieved for O‐IDTBR transistors upon optimal doping with DQ. The enhanced performance originates primarily from synergistic effects on electronic transport and changes in morphology, including: i) significant reduction of contact resistances, ii) formation of larger crystalline domains, iii) change of preferred crystal orientation, and iv) alteration in molecular packing motif. This work demonstrates the universality of DQ as an electronic additive for improving electron transport in OTFTs. Abstract : The use of the molecular n ‐dopant diquat (DQ) in several solution‐processed non‐fullerene acceptor molecules, is demonstrated. The presence of DQ leads to major enhancement in the electron mobility across all molecules, reaching a maximum value of >1 cm 2  V −1  s −1 for O‐IDTBR. The improvement is shown to originate from the suppressed contact resistance and the synergistic microstructural changes induced by the dopant.